2015
DOI: 10.3892/mmr.2015.4603
|View full text |Cite
|
Sign up to set email alerts
|

Rhus javanica Linn protects against hydrogen peroxide-induced toxicity in human Chang liver cells via attenuation of oxidative stress and apoptosis signaling

Abstract: Rhus javanica Linn, a traditional medicinal herb from the family Anacardiaceae, has been used in the treatment of liver diseases, cancer, parasitic infections, malaria and respiratory diseases in China, Korea and other Asian countries for centuries. In the present study, the protective effects of R. javanica ethanolic extract (RJE) on hydrogen peroxide (H2O2)-induced oxidative stress in human Chang liver cells was investigated. The cell cytotoxicity and viability were assessed using a 3-(4,5-dimethylthiazol-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Four articles studying the use of anti-malarial medicines conventionally used in traditional Eastern Asian medicines (previously listed) reported cytotoxicity towards cancer cells, mainly through inducing apoptosis. Notably, three of the medicines studied (excluding ASLRB) interacted with caspases in its anti-cancer mechanisms, with RJL and PK extract regulating caspase-3 expression among other pro-apoptotic genes while Harmol activated caspase-8 [ 87 – 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Four articles studying the use of anti-malarial medicines conventionally used in traditional Eastern Asian medicines (previously listed) reported cytotoxicity towards cancer cells, mainly through inducing apoptosis. Notably, three of the medicines studied (excluding ASLRB) interacted with caspases in its anti-cancer mechanisms, with RJL and PK extract regulating caspase-3 expression among other pro-apoptotic genes while Harmol activated caspase-8 [ 87 – 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the study indicated that the extract could protect human liver cells against oxidative damage by increasing the antioxidant enzyme levels and regulating the antiapoptotic oxidative stress mechanisms. 32 Another study reported that Sumac extract exhibited strong activity against nitric oxide and reactive oxygen species. Furthermore, the extract significantly regulated the expression of nitric oxide synthase, which prevents COULD SUMAC BE EFFECTIVE ON COVID-19 TREATMENT?…”
Section: Antioxidant and Liver-protective Effectmentioning
confidence: 99%
“… 2006 ; Yoon et al. 2016 ). Therefore, it is important to induce the apoptosis of HSCs or prevent the secretion of the ECM by HSCs (Lee et al.…”
Section: Introductionmentioning
confidence: 99%